OTONOMI PENDIDIKAN BERBASIS DEMOKRATISASI DAN BUDAYA ETOS KERJA - A. Ubaedi Fathuddin (Jurnal Forum Tarbiyah, 2010)
The development of education in the era of regionalautonomy requires the implementation of democratic values andculture of work ethic. Democratization of education will encouragelocal people to be citizens who understand the rights of life and arenot easily exploited. Meanwhile, the development of the work ethicculture through education is assumed to be fundamentally impact onvarious aspects of local community life. The combination of both theautonomy of education will create a clean Government which isparticipative, innovative and independent